CLINICO-PATHOLOGICAL AND GENETIC STUDY OF FAMILIAL TRANSTHYRETIN-TYPE AMYLOID POLYNEUROPATHY - Parman, Y.; Matur, Z.; Shugaiv, E.; Ilgaz\\-Aydinlar, E.; Battaloglu, E.; Oflazer, P.; Deymeer, F. (WILEY-BLACKWELL, 2011)
Meeting of the Peripheral-Nerve-Society, Potomac, MD, JUN 25-29, 2011